Jurnal Rancang Bangun Media Pembelajaran Ilmu Nahwu Berbasis Website: Studi Kasus : Pesantren Al Bukhori Brebes - Muhammad Ahsan Jamil; Rosidin Rosidin; Sukarsa Sukarsa; Dicky Andika Sulaeman; Akhmad Purnamaysah (LPPM UNU CIREBON, 2025)
The 21st century is characterized by rapid advancements in information technology, impacting various aspects of life, including education systems. In this context, educational media plays a crucial role in enhancing the effectiveness of communication between educators and learners. Pesantren Al Bukhori, an Islamic educational institution in Brebes Regency, still relies on conventional methods for teaching Ilmu Nahwu, which limits learning within specific spaces and times. This research, titled